1989
DOI: 10.1148/radiology.170.1.2909085
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative dual-energy radiographic absorptiometry of the lumbar spine: in vivo comparison with dual-photon absorptiometry.

Abstract: Quantitative dual-energy radiographic absorptiometry (DRA) and dual-photon absorptiometry (DPA) were compared to determine the best means of assessing bone density. Both methods were used to evaluate the lumbar spine in 107 women (aged 35-84 years [mean, 64 years]) referred for evaluation of osteoporosis risk. High correlation was documented between measurements derived by the two techniques, with a .95 linear regression coefficient for the total spine density measurement. Age-related regression equations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1989
1989
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(12 citation statements)
references
References 0 publications
1
10
0
1
Order By: Relevance
“…Our study is the first one assessing the precision of DEXA of the proximal femur by repeated measurements both in young and in elderly women. The results confirm the higher precision obtained with X-ray absorptiometry, 1% for the femoral neck in the elderly, a number which is similar to the precision of the lumbar spine measurement [13][14][15]. The lower precision of the Ward's triangle region might be due to the fact that the bone mineral content of this limited area is very small.…”
Section: Fractured Patientssupporting
confidence: 81%
“…Our study is the first one assessing the precision of DEXA of the proximal femur by repeated measurements both in young and in elderly women. The results confirm the higher precision obtained with X-ray absorptiometry, 1% for the femoral neck in the elderly, a number which is similar to the precision of the lumbar spine measurement [13][14][15]. The lower precision of the Ward's triangle region might be due to the fact that the bone mineral content of this limited area is very small.…”
Section: Fractured Patientssupporting
confidence: 81%
“…Other authors [7,8] also found lower BMD in men who had undergone partial gastrectomy (85%) and total gastrectomy (86%) than in the control population. Recently, DXA was introduced for the quantitative analysis of metabolic bone disease [11,12]. Inoue et al [14] demonstrated that BMD in gastrectomized patients (0.85 g/cm 2 ) is significantly lower than that in healthy men (0.96 g/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since DXA has high resolution and great speed, and permits accurate and reproducible measurements [11,12], this noninvasive method clinically serves as a useful technique for identifying and treating osteoporosis [13,14].…”
mentioning
confidence: 99%
“…Other investigations to determine the accuracy of DXA have compared this technology with either dual photon absorptiometry or hydroxyapatite phantoms of known density [8,9,12,13]. Although these methods appear reasonable to assess the ability of DXA to determine mineral content, they do not provide information concerning DXA's ability to distinguish between the variations in cortical and cancellous bone that occur with age.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have attempted to describe the accuracy of DXA in terms of a correlation with dual photon absorptiometry, a technology that is highly correlated with ash weight [11]. These studies have found significant positive relationships, with Pearson coefficients above 0.9 when DXA BMD and dual photon absorptiometry BMD measurements from the same bone were correlated [9,12,13]. The ability of DXA to measure BMD accurately has been questioned in the literature, as it does not provide a true volumetric bone density (g/cm 3 ) but rather an areal density (g/cm 2 ).…”
Section: Introductionmentioning
confidence: 99%